Coral spawning patterns on the Luhuitou fringing reef in Hainan Island of the northern South China Sea - Sun, Youfang; Zhang, Yuyang; Jiang, Lei; Yu, Xiaolei; Huang, Lintao; Yuan, Tao; Yang, Jianhui; Lian, Jiansheng; Liu, Chengyue; Ang, Put; Huang, Hui (Frontiers in Marine Science, 2024)
Observation of coral spawning times is valuable to detect spawning patterns and identify the potential mechanisms behind coral reproduction. Although large amount of data on global coral spawning records have become available over the past decades, information on coral spawning in the northern South China Sea remains scarce. In this study, we investigated the spawning patterns of scleractinian corals in Luhuitou fringing reef, Hainan Island, China, from 2009 to 2021 in relation to lunar cycles (month and day). The spawning times of 22 coral species from five genera (Acropora, Montipora, Platygyra, Dipsastraea, and Galaxea) within three families (Acroporidae, Merulinidae, and Euphylliidae) were recorded, with spawning occurring from lunar February to May 2009–2021. Recorded spawning events started at a period of increasing seawater temperature. Acropora, the most documented genus, spawned between lunar February and April, but primarily in lunar March. Importantly, the spawning time of Acropora was delayed for one lunar month in 2016 most likely due to a rapid decrease in monthly mean seawater temperature in lunar February. Spawning lunar days before, on or after full moon of corals in the Luhuitou Reef, including those of the Acropora species, were highly variable between years even for the same species. No predictable pattern of spawning times can thus be detected. Nonetheless, our results fill up an information gap on coral spawning patterns in the northern South China Sea that may be useful for further understanding of the reproductive biology of scleractinian corals throughout the Indo–West Pacific.